Benefits, equity, and sustainability of community rainwater harvesting structures: An assessment based on farm scale social survey - Alam, Mohammad Faiz; McClain, Michael E.; Sikka, Alok; Daniel, D.; Pande, Saket (Frontiers in Environmental Science, 2022)
Rainwater harvesting systems (RWHs) are implemented globally to bridge the frequent water supply-demand gaps. This study explores, through farmer household surveys (n = 492), how farmers perceived the benefits of RWHs, the equitability of benefits, and the role of contextual and psychological factors towards the behaviour of maintaining such systems. The study is carried out in a semi-arid catchment in the Indian state of Gujarat where RWHs, in the form of Check dams (CDs), have been implemented extensively. Results show that the benefits of CDs are perceived in good rainfall years through enhanced availability of water for expanding crops and irrigated areas. Farmers reported limited benefits of CDs in dry years. This is because of limited runoff and no carryover of stored groundwater, due to underlying shallow hard rock aquifer with little primary porosity, from wet years to dry years. Overall, ~ 40-50 % of sampled farmers reported no benefits from CDs and the benefits decreased with distance. This reflects a spatially inequitable distribution of benefits skewed towards the farmers nearest to the CDs. The sustainability of CDs is a challenge with already ~ 40 % of CDs reportedly not working and 72.8 % of farmers reported doing no maintenance activity. This is because 91.2 % of farmers reported playing no role in its construction. The results show contextual (participation during construction, economic indicators) and sociopsychological factors (attention to CD condition, maintenance effort) significantly affect the behaviour towards maintaining the CDs. This highlights the need to complement RWHs with wider drought management and water demand management interventions to achieve drought resilience, and adherence to project exit protocols to secure the sustainability of investments.